Upaya Revitalisasi Permukiman Tradisional Tepi Sungai (Studi Kasus : Permukiman Kampung Tenun Samarinda) - Hayuni, Nurvina; Syahbana, Joesron Alie (Magister Pembangunan Wilayah dan Kota,Undip, 2014)
Kampung Tenun is the representatives of the first settlement in Samarinda that located on the edge of the Mahakam River. In 2012, there was the government's program to revitalize the on Kampung Tenun. Based on the description, it is necessary to discuss more about the revitalization and how the potential of Kampung Tenun related its existence as a riverfront area. The aim of this observation is to analyze the extent of the policy of the goverment in revitalizing neighborhoods andÂ to analyze the potential development of the village as a riverfront area. This research was conducted through interviews with relevant stakeholders using snowball sampling technique and purposive sampling. The next stage is conducted a qualitative descriptive analysis method using the variables of revitalization and the development of waterfront activities. The conclusion of this study is that the succesÂ of the weaving village revitalization program is quite successful in terms of physical intervention, but there are still some shortcomings in the process of economic rehabilitation and social engineering. Therefore, it is suitable to be developed into a mixed-use waterfront neighborhood that accommodates all kinds of potential Kampung Tenun to be the riverfront area of competitive and sustainable.